Sentiment Analysis of the Enforcement of PSBB Part II in Jakarta - Brahmantha, Gede Putra Aditya; Santiyasa, I Wayan (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 9 No 2 (2020): JELIKU Volume 9 No 2, November 2020, 2020)
In addition to communicating, Social Media is a place to issue opinions by the public on many things that are currently taking place, Twitter is one of these social medias that is widely used in conveying opinions regardless of whether these opinions are negative, positive, or even neutral. Tweets data about the Enforcement of PSBB Part II in Jakarta were obtained as many as 200 opinions using web crawling then advanced to the preprocessing stage before being classified using the K-Nearest Neighbor and Multinomial Naive Bayes algorithms. In 3 tests, the highest accuracy was 65.00% for K-Nearest Neighbor and the highest accuracy was 85.00% for Multinomial Naive Bayes method.